2019
DOI: 10.1186/s40824-019-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of nanoparticles and routes of administration

Abstract: In modern-day medicine, nanotechnology and nanoparticles are some of the indispensable tools in disease monitoring and therapy. The term “nanomaterials” describes materials with nanoscale dimensions (< 100 nm) and are broadly classified into natural and synthetic nanomaterials. However, “engineered” nanomaterials have received significant attention due to their versatility. Although enormous strides have been made in research and development in the field of nanotechnology, it is often confusing for beginners t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
418
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 752 publications
(422 citation statements)
references
References 251 publications
(270 reference statements)
4
418
0
Order By: Relevance
“…Particles with non-spherical geometry can be fabricated using de novo methods like film stretching or template assembly [ 53 ]. It has been demonstrated that non-spherical NPs tumble with the flow while the symmetric spherical NPs move more easily [ 54 ]. There are contradictory data on cellular uptake of NPs depending on size.…”
Section: Physico-chemical Aspects Of the Protein Corona Formationmentioning
confidence: 99%
“…Particles with non-spherical geometry can be fabricated using de novo methods like film stretching or template assembly [ 53 ]. It has been demonstrated that non-spherical NPs tumble with the flow while the symmetric spherical NPs move more easily [ 54 ]. There are contradictory data on cellular uptake of NPs depending on size.…”
Section: Physico-chemical Aspects Of the Protein Corona Formationmentioning
confidence: 99%
“…Some studies demonstrated that phosphatidylcholine (PC) is capable of interacting with the negatively charged (acidic) compounds when incorporated into lms, leading to the adverse effects on the drug release pro le when used in the tumor microenvironment. On the other hand, incorporation of polyethylene glycol (PEG) into the surface of liposomes has been demonstrated to be useful in increasing the stability of formulations, controlled release rate, prolonging the half-life of the drug in the bloodstream, and preventing the uptake of nanocarriers by the reticuloendothelial system (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles can be administered by various routes, including oral, parenteral, and pulmonary inhalation depending upon the disease state, the drug target, patient compliance, and the material and surface properties of nanomaterials [ 54 ]. Among these, oral and intravenous administration are the two most common routes of administration of NPs.…”
Section: Nanoparticle-mediated Tumor Targetingmentioning
confidence: 99%